Evaluating the Effect of Manufacturing Porcine Epidemic Diarrhea Virus (PEDV)-Contaminated Feed on Subsequent Feed Mill Environmental Surface Contamination - L. L. Schumacher; R. A. Cochrane; C. E. Evans; J. R. Kalivoda; J. C. Woodworth; C. R. Stark; C. K. Jones; Rodger G. Main; Jianqiang Zhang; S. S. Dritz; Phillip Charles Gauger (Kansas Agricultural Experiment Station Research Reports, 2015)
This study aimed to utilize the only known pilot feed mill facility approved for pathogenic feed agent use in the United States to evaluate the effect of manufacturing Porcine Epidemic Diarrhea Virus (PEDV)-contaminated feed on subsequent feed mill environmental surface contamination. In this study, PEDV inoculated feed was manufactured and conveyed on equipment along with four subsequent batches of PEDV-free feed. Equipment and environmental surfaces were sampled using swabs and analyzed for the presence of PEDV RNA by PCR. The experiment was replicated three times with decontamination of the feed mill and all equipment between replications. Overall, environmental swabs indicated widespread surface contamination of the equipment and work area after a PEDV contaminated batch of feed was processed. There was little difference in environmental sample cycle threshold (Ct) values after manufacturing each of the subsequent PEDV-negative feed batches. In summary, introduction of PEDV-infected feed into a feed mill will likely result in widespread contamination of equipment and surfaces, even after several batches of PEDV-free feed are produced. Eliminating the PEDV RNA from the feed mill environment was challenging and required procedures that are not practical to apply on a regular basis in a feed mill. This data suggests that it is extremely important to prevent the introduction of PEDV-contaminated feed, ingredients, or other vectors of transmission to minimize PEDV-risk. More research should be conducted to determine if contaminated surfaces can lead to PEDV infectivity and to determine the best feed mill PEDV-decontamination strategies.
Keywords: PEDV; feed mill; decontamination; swabs; PCR